Cause of an extreme warm and rainy winter in Shanghai in 2019. (27th March 2021) - Pan, Xiao; Wang, Wei; Li, Tim; Xin, Fei; Yu, Jinhua
Abstract: An extreme warm winter (ranked first during the past 30‐years) occurred in Shanghai in 2019, accompanied with an extreme rainy winter (ranked thirdly in the same period). An observational diagnosis shows that the extreme warm and rainy winter arose from southerly anomalies associated with an anticyclone east of Shanghai. The cause of the anticyclone was attributed to V‐shaped upper‐tropospheric Rossby wave activity fluxes, originated from the North Atlantic and tropical Indian Ocean. Numerical model experiments indicate that the anomalous heat source in the tropical Indian Ocean played a dominant role ( 65%) in causing the local anomalous circulation, while the heating in North Atlantic also played a role ( 35%). A further analysis of the past 30 year data revealed that an extreme warm winter in the past did not coincide with an extreme wet winter. While the warm winter composite shows a large‐scale anticyclone anomaly over Central and East Asia, the rainy winter composite exhibits a circulation dipole pattern with an anomalous cyclone (anticyclone) west (east) of Shanghai. Numerical experiments confirm that the former was forced by the combined effect of precipitation anomalies over the North Atlantic and tropical Indian Ocean (IO) and Maritime Continent (MC) through Rossby wave energy dispersion, whereas the latter was caused by a dipole heating pattern over the tropical IO/MC sector. Abstract : Observational diagnosis shows that the extreme warm and rainy winter in Shanghai in 2019 arose from southerly anomalies associated with an anticyclone, which was attributed to V‐shaped upper‐tropospheric Rossby wave activity fluxes, originated from the North Atlantic and the tropical Indian Ocean. Numerical model experiments indicate that the anomalous heat source in the tropical Indian Ocean played a dominant role ( 65%) in causing the local anomalous circulation, while the heating in North Atlantic also played a role ( 35%). Further analysis revealed that an extreme warm winter in the past did not coincide with an extreme wet winter.